Macrosystem community change in lake phytoplankton and its implications for diversity and function - Benjamin Weigel; Niina Kotamäki; Olli Malve; Kristiina Vuorio; Otso Ovaskainen (Global Ecology and Biogeography, 2023)
Aim We use lake phytoplankton community data to quantify the spatio‐temporal and scale‐dependent impacts of eutrophication, land‐use and climate change on species niches and community assembly processes while accounting for species traits and phylogenetic constraints. Location Finland. Time period 1977–2017. Major taxa Phytoplankton. Methods We use hierarchical modelling of species communities (HMSC) to model metacommunity trajectories at 853 lakes over four decades of environmental change, including a hierarchical spatial structure to account for scale‐dependent processes. Using a “region of common profile” approach, we evaluate compositional changes of species communities and trait profiles and investigate their temporal development. Results We demonstrate the emergence of novel and widespread community composition clusters in previously more compositionally homogeneous communities, with cluster‐specific community trait profiles, indicating functional differences. A strong phylogenetic signal of species responses to the environment implies similar responses among closely related taxa. Community cluster‐specific species prevalence indicates lower taxonomic dispersion within the current dominant clusters compared with the historically dominant cluster and an overall higher prevalence of smaller species sizes within communities. Our findings denote profound spatio‐temporal structuring of species co‐occurrence patterns and highlight functional differences of lake phytoplankton communities. Main conclusions Diverging community trajectories have led to a nationwide reshuffling of lake phytoplankton communities. At regional and national scales, lakes are not single entities but metacommunity hubs in an interconnected waterscape. The assembly mechanisms of phytoplankton communities are strongly structured by spatio‐temporal dynamics, which have led to novel community types, but only a minor part of this reshuffling could be linked to temporal environmental change.